Automating untruths: ChatGPT, self-managed medication abortion, and the threat of misinformation in a post-Roe world - McMahon, Hayley V.; McMahon, Bryan D. (Frontiers in Digital Health, 2024)
Background: ChatGPT is a generative artificial intelligence chatbot that uses natural language processing to understand and execute prompts in a human-like manner. While the chatbot has become popular as a source of information among the public, experts have expressed concerns about the number of false and misleading statements made by ChatGPT. Many people search online for information about self-managed medication abortion, which has become even more common following the overturning of Roe v. Wade. It is likely that ChatGPT is also being used as a source of this information; however, little is known about its accuracy.Objective: To assess the accuracy of ChatGPT responses to common questions regarding selfmanaged abortion safety and the process of using abortion pills.We prompted ChatGPT with 65 questions about self-managed medication abortion, which produced approximately 11,000 words of text. We qualitatively coded all data in MAXQDA and performed thematic analysis.Results: ChatGPT responses correctly described clinician-managed medication abortion as both safe and effective. In contrast, self-managed medication abortion was inaccurately described as dangerous and associated with an increase in the risk of complications, which was attributed to the lack of clinician supervision.ChatGPT repeatedly provided responses that overstated the risk of complications associated with self-managed medication abortion in ways that directly contradict the expansive body of evidence demonstrating that self-managed medication abortion is both safe and effective. The chatbot's tendency to perpetuate health misinformation and associated stigma regarding selfmanaged medication abortions poses a threat to public health and reproductive autonomy.